STRATEGI LEMBAGA PARISADA DALAM PENEGAKAN HUKUM HINDU DI TENGAH INTERAKSI SOSIAL MASYARAKAT KECAMATAN BASARANG KABUPATEN KAPUAS - I Made Kastama (Belom Bahadat, 2022)
This type of research was qualitatively descriptive with the objective for analyzing the strategies carried out by the Parisada institution in Hindu law enforcement in the midst of social interaction of the people of Basarang sub-district of Kapuas Regency. The informant in this study was the administrator of Parisada Hindu Dharma Indonesia (PHDI) Basarang sub-district. This research was conducted by means of in-depth interviews and the data obtained was analyzed and described in the form of words. The conclusion of this research was that the strategy of the Parisada institution in the enforcement of Hindu Law in the midst of social interaction in Basarang District of Kapuas Regency was carried out in an organizational approach by demonstrating its role as a supervisory institution and community organizer with its authority to enforce Hindu law with restrictions on the Articles of Association of Parisada Province and Central Parisada. Activities applied to all activities of Hindu society refered to the constitutionalized Hindu Law in awig-awig. Arrangements in marriage, arrangements in yadnya arrangements in divorce, arrangements in inheritance and other issues were regulated by awig-awig as legal guidelines sourced from the Vedas and Manawadharma literature. The strategy of the Parisada institution in resolving the problem of violations of Hindu law, if the violation entered the realm of custom, then Parisada as a partner of the Customs Council in resolving the problem by mediating it. Parisada as a partner of Kelihan Adat in resolving problems through mediation. If in solving the problem Kelihan adat cannot solve it, then the problem was delegated to Parisada to resolve it with the authority to be in the Parisada institution to resolve it until a decision was made by the Parisada institution with a strategy of deciding cases based on Hindu legal considerations.